(untitled) (International Journal of Engineering and Computer Science, 2017)
The purpose is used to plan and grow an agricultural system based on arduino method. The arduino chip was used in combination with sensors to measure ecological factors namely the temperature, humidity and soil moisture. The data’s are sent to the farmer through message from the cloud based on necessities used by weed detection algorithm. This will be estimated to supportive for farmers in the order of the state.